Pathogenesis of SARS-CoV-2 and Mycobacterium tuberculosis Coinfection - Shah, Taif; Shah, Zahir; Yasmeen, Nafeesa; Baloch, Zulqarnain; Xia, Xueshan (Frontiers in Immunology, 2022)
Coronavirus disease-2019 (COVID-19), caused by SARS-CoV-2, is an infectious disease that poses severe threats to global public health and significant economic losses. The COVID-19 global burden is rapidly increasing, with over 246.53 million COVID-19 cases and 49.97 million deaths reported in the WHO 2021 report. People with compromised immunity, such as tuberculosis (TB) patients, are highly exposed to severe COVID-19. Both COVID-19 and TB diseases spread primarily through respiratory droplets from an infected person to a healthy person, which may cause pneumonia and cytokine storms, leading to severe respiratory disorders. The COVID-19-TB coinfection could be fatal, exacerbating the current COVID-19 pandemic apart from cellular immune deficiency, coagulation activation, myocardial infarction, and other organ dysfunction. This study aimed to assess the pathogenesis of SARS-CoV-2-Mycobacterium tuberculosis coinfections. We provide a brief overview of COVID19-TB coinfection and discuss SARS-CoV-2 host cellular receptors and pathogenesis. In addition, we discuss M. tuberculosis host cellular receptors and pathogenesis. Moreover, we highlight the impact of SARS-CoV-2 on TB patients and the pathological pathways that connect SARS-CoV-2 and M. tuberculosis infection. Further, we discuss the impact of BCG vaccination on SARS-CoV-2 cases coinfected with M. tuberculosis, as well as the diagnostic challenges associated with the coinfection.